2018
DOI: 10.1016/j.bmcl.2018.01.044
|View full text |Cite
|
Sign up to set email alerts
|

Activation loop targeting strategy for design of receptor-interacting protein kinase 2 (RIPK2) inhibitors

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…A-loop interactions remain a curiosity among kinase inhibitors but have been reported in some cases and the potential for target selectivity discussed [ 9 ]. Here, we demonstrate that stabilization of A-loop interactions may give rise to both exquisite selectivity, as well as a specific kinetic profile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A-loop interactions remain a curiosity among kinase inhibitors but have been reported in some cases and the potential for target selectivity discussed [ 9 ]. Here, we demonstrate that stabilization of A-loop interactions may give rise to both exquisite selectivity, as well as a specific kinetic profile.…”
Section: Discussionmentioning
confidence: 99%
“…Binding to the back pocket allows for contacts between small molecule inhibitor and the kinase activation loop (A-loop). Such interactions have been described for several kinases, including c-Met, MEK1, RIPK1 and RIPK2 (reviewed by [ 9 ]), and can contribute to both binding potency and kinome selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…This work is the first to demonstrate the efficacy and modulatory activity of a RIP2 targeting compound using a clinically relevant model of allergic asthma. Numerous inhibitors have both been discovered and developed for modulation of RIP2 activity (23,(35)(36)(37)(38)(39)(40)(41)(42)(43). The RIP2 inhibitor utilized in this study, GSK583, has been reported to be highly selective and exhibits strong potency even in vivo (23,39).…”
Section: Discussionmentioning
confidence: 99%
“…The structural model of the RIPK2-MKK7 complex was generated from available structures in the RCSB Protein Data Bank (PDB) 48 . Briefly, the 3D structure of the RIPK2 kinase domain was used from an available structure (PDB code 6ES0) 49 , and that of the MKK7 kinase domain was generated by homology modelling 50 , using the structure of MEK1 (PDB code 1S9I) 51 as a template. Putative dimerization models of kinase domains were generated with Rosetta 52 and ZDOCK 53 .…”
Section: Interactome Analysis By Immunoprecipitation-mass Spectrometrmentioning
confidence: 99%